(untitled) (Journal of Social Sciences Review, 2024)
Organizations are confronted with work alienation among workers, yet there is limited empirical research on how work alienation varies based on age and work experience. This study evaluated the difference in work alienation by age and work experience among agricultural knowledge workers. Using stratified sampling technique, data were collected from 350 respondents. Data were collected through in-person visits and Google forms. Kruskal Wallis test and Bonferroni correction methods were used to evaluated the study hypotheses. The results demonstrated that there are statistically significant differences in work alienation across various age and experience groups of agricultural knowledge workers. The study findings underscore the importance of sociodemographic factors in understanding the processes of work alienation. The study contributes to the existing knowledge of sociodemographic and socioeconomic factors contributing to work alienation and work engagement among various groups of agricultural knowledge workers.